PERILAKU ENTREPRENEUR PENGRAJIN GULA KRISTAL DI WILAYAH PERDESAAN - Sulistyani Budiningsih; Watemin Watemin (Universitas Muhammadiyah Purwokerto, 2014)
Objective of this research 1) knowing the characteristics of entrepreneurial actors crystal sugar producers, 2) to analyze the behavior of the entrepreneur craftsmen crystal sugar in the District Cilongok Banyumas.The location of research in Sub District Cilongok Banyumasset intentionally (purposive sampling) with consideration of a center of crystal sugar. Source of research date in the form of primary and secondary date. Date was collected through interviews, observation and documentation. Date analysis with qualitative descriptive analysis techniques and quantitative analysis. To identify the characteristics of the entrepreneur farmers and craftsmen used descriptive method of analysis simple statistic. In studying the distribution of the factors that influence the behavior of the entrepreneur craftsmen crystal sugar quantitatively analyzed descriptively. Results The average number of coconut trees entrepreneurial ownership crystal sugar producers reached 23 trees with ownership system consists of one's own and lease tree from others. The results showed that there were 9 (22%) of respondents who have their own trees and also hire other people's trees. While 31 (77%) of respondents are craftsmen who rely on privately owned palm trees to be taken niranya. Formal education is the average respondent Graduated Elementary School: 29 respondents (72.5%), followed by junior high school graduated 10 respondents (25%) and graduated from high school there is only one respondent (2.5%). Age of respondents actors Cilongok entrepreneur craftsmen in the district known that most or at (100.00 percent), including the productive age group with a mean age of 46.25 years. Productivity is still low, it can be seen from the average - average number of respondents production craftsmen new farmers can achieve a production of 4.69 kg per day and 140.66 kg per month. Experience crystal sugar craftsman entrepreneur vary, there are just starting a business that is less than 1 year and there are craftsmen who have more than 5 years in the business this long with an average of 3 years 6 months entrepreneurship. Keywords :behavior, entrepreneur, crystal sugar, rural